Students' Mathematical Communication Skills Through Learning 4k Models To Improve The Character Of Curiosity - Moh Saironi; Busiri A H (Jurnal Sosial Teknologi, 2023)
In essence, every human being must always communicate, but the level of breadth of communication will always be different. Communicating that is more meaningful is determined by the level of one's thinking ability. Thinking more creatively and innovatively in dealing with problems and situations will not be possessed without extensive knowledge. The goal of mathematics is that students have the ability to understand mathematical concepts, use reasoning, solve problems, communicate ideas, and have an attitude of appreciating the usefulness of mathematics in life. This study used techniques and methods of systematic literature review or also known as literature review. The method used for data collection techniques is conducting a literature study, then identifying, studying, evaluating, and interpreting the available research, literature books, and reports. As a result of the maximum educational process, teacher activity is needed in choosing learning strategies. The obligation as an educator, is not only to transfer knowledge, but also to change the behavior and character of students and provide positive encouragement, so that students are motivated to provide a pleasant learning atmosphere so that they can develop as much as possible. The conclusion is that the selection of learning strategies to be used in the learning process must be oriented towards the learning objectives to be achieved. In addition, it must be adjusted to the type of material, the characteristics of students, the conditions in which the learning process will take place.